Utilization of Financial Technology Services to Increase Business Sustainability for MSMEs in Demak Regency - Siti Shobandiyah; Septia Kurniati; Astohar Astohar (Management Analysis Journal, 2023)
Financial technology in Indonesia is currently developing very rapidly marked by the innovation of several applications in the field of financial services such as payment instruments, loan instruments and others that are becoming known in this digital era. Several business actors such as MSMEs in Demak Regency have also utilized this financial technology (fintech) to make it easier to run businesses. The survey results show that MSMEs are still not optimal in using fintech and the level of inclusion is still relatively low. The population in this study were all UMKM in the District of Demak Regency. Collecting data using cross sectional data with the sampling method using accidental sampling. The analysis tool uses multiple step multiple regression by carrying out other tests such as the normality test, the classical assumption deviation test, the fit test and the coefficient of determination test. The results of the study show that financial literacy has a significant positive effect on financial inclusion. Fintech-based financial services have a significant positive effect on financial inclusion. Financial skills have a significant positive effect on financial inclusion. MSMEs that are able to utilize financial technology are more capable of sustainability in business.